New pre-arrival instructions can avoid abdominal hand placement for chest compressions - Birkenes, Tonje S (BioMed Central, 2013)
OBJECTIVE: To investigate if modified pre-arrival instructions using patient’s arm and nipple line as landmarks could avoid abdominal hand placements for chest compressions. METHOD: Volunteers were randomized to one of two telephone instructions: “Kneel down beside the chest. Place one hand in the centre of the victim’s chest and the other on top” (control) or “Lay the patient’s arm which is closest to you, straight out from the body. Kneel down by the patient and place one knee on each side of the arm. Find the midpoint between the nipples and place your hands on top of each other” (intervention). Hand placement was conducted on an adult male and documented by laser measurements. Hand placement, quantified as the centre of the compressing hands in the mid-sagittal plane, was compared to the inter-nipple line (INL) for reference and classified as above or below. Fisher’s exact test was used for comparison of proportions. RESULTS: Thirty-six lay people, age range 16–60, were included. None in the intervention group placed their hands in the abdominal region, compared to 5/18 in the control group (p = 0.045). Using INL as a reference, the new instructions resulted in less caudal hand placement, and the difference in mean hand position was 47 mm [95% CI 21,73], p = 0.001. CONCLUSION: New pre-arrival instructions where the patient’s arm and nipple line were used as landmarks resulted in less caudal hand placements and none in the abdominal region.